Optimizing engagement in goal pursuit with youth with physical disabilities attending life skills and transition programs: an exploratory study. Issue 20 (25th September 2017) - Smart, Eric; Aulakh, Adeeta; McDougall, Carolyn; Rigby, Patty; King, Gillian
Abstract: Purpose: Identify strategies youth perceive will optimize their engagement in goal pursuit in life skills and transition programs using an engagement framework involving affective, cognitive, and behavioral components. Methods: A qualitative descriptive design was used. Two semi-structured interviews were conducted with seven youth. The first was informed by a prior observation session, and the second occurred after the program ended and explored youths' perceptions of whether and how their engagement changed. Data were analyzed using thematic analysis. Results: The analysis generated eight strategies youth considered effective. These were categorized under the three components of engagement. Affective strategies: (1) building a relationship on familiarity and reciprocity; and (2) guiding the program using youths' preferences and strengths. Cognitive strategies: (3) assisting youth to envision meaningful change; (4) utilizing youths' learning styles; and (5) promoting awareness of goal progress. Behavioral strategies: (6) ensuring youth access to a resource network; (7) providing youth multiple decision opportunities; and (8) enabling youth to showcase capabilities. Conclusions: Service providers together with youth are encouraged to consider the role of context and self-determination needs in order to optimize youth engagement in goal pursuit. Systematic approaches to studying engagement are necessary to learn how to maximize rehabilitation potential. Implications for Rehabilitation: Service providers are encouraged to be aware of the nature of engagement strategies identified by youth. Comprehensive frameworks of engagement are essential to generate knowledge on the range of strategies service providers can use to engage clients in rehabilitation services. Strategies perceived by youth to optimize their engagement in goal pursuit in life skills and transition programs have subtle yet significant differences with strategies used in other rehabilitation settings like mental health and adult healthcare services. Self-determination theory shows potential in guiding further research on exploring the role of engagement in maximizing rehabilitation outcomes.